Novel Transoral Endoscopic Assisted Minimally Invasive Method for Mandibular Condyle Fractures in Croatia: A Case Presentation and Literature Review - Igor Čvrljević; Marko Tarle; Ivica Lukšić (Acta Stomatologica Croatica)
Mandibular fractures, particularly condylar process fractures, are common in maxillofacial surgery and require effective treatment methods that minimize complications while ensuring functional and esthetic recovery. Objectives: This paper presents two cases of mandibular condylar process fractures treated using a transoral endoscopically assisted technique (EATA), thus marking the first documented application of this approach in Croatia. The aim was to evaluate the efficacy of this minimally invasive method compared to traditional extraoral approaches, which often carry risks such as visible scarring, facial nerve injury, and prolonged postoperative recovery. Methods: A 30° rigid endoscope and specialized angled instruments were utilized in both cases to achieve precise visualization, reduction, and fixation of the fractures. The first case involved a young male with a double mandibular fracture, while the second case addressed an isolated condylar fracture in an older female with comorbidities. Results: Both patients were successfully treated without complications, including facial nerve injury, hematomas, or salivary fistulas. Hospitalization periods were shorter compared to traditional approaches, and recovery included restored temporomandibular joint function (TMJ), stable occlusion, and the absence of visible scars. The EATA method proved to be safe and effective, offering numerous advantages such as reduced morbidity, minimal soft tissue trauma, and superior aesthetic outcomes. Despite requiring specialized equipment and additional surgical training, EATA has significant potential to become a standard treatment modality for mandibular fractures. Conclusion: The findings of this study contribute to the growing body of evidence supporting the clinical benefits of this minimally invasive technique.